BEYOND THE NUMBER: TONE ANALYSIS IN ANNUAL REPORTS - Suryani, Ani Wilujeng; Fauz, Dinda Tustika Apta (Jurnal Akuntansi dan Keuangan Indonesia, 2024)
In making decisions, stakeholders utilize not only quantitative information but also qualitative information, such as annual reports. However, annual reports in narrative form are often used to exaggerate company performance data. One aspect that influences stakeholders’ decision is tone. This study aims to examine the impact of positive tone disclosure in management analysis reports and discussions on company value. This study was conducted on 166 financial and property companies listed on the IDX. Management analysis and discussion reports were categorized according to their tone. Using linguistic inquiry and word count software (LIWC-22), the procedure yielded more precise and consistent analysis. Financial data used to determine the value of company was the price-to-book-value (PBV) ratio. The results of the test using robust regression analysis showed that the positive tone disclosure with an informative nature had a positive influence on the company’s value. This finding suggests that managers must use positive tones when regulating the company's situation in order to maintain the expected value of company.